Diagnostic challenge of Pneumocystis jirovecii pneumonia infection mimicking interstitial lung disease in initially HIV negative patient - Kristy, Anastasia; Yaniswari, Ni Made Dwita (Jurnal Prima Medika Sains, 2023)
Background: Pneumocystis jirovecii pneumonia (PJP) infections are common in immunocompromised patients and are rarely found in immunocompetent patients. Lung radiology in PJP patients could mimic the appearance of interstitial lung disease (ILD) and could be used to diagnose HIV-negative patients. Clinicians should rule out false negatives in patients with patterns suggestive of opportunistic infections and risk factors for HIV infection. Case illustration: A 34-year-old man presented with a chief complaint of shortness of breath, had history of 15 years of smoking, and daily chlorine exposure. The radiology pattern and initial HIV-negative test results suggested an ILD diagnosis. Owing to persistent symptoms despite initial management and the presence of risk factors, repeat HIV testing was initiated and was positive. The patient was treated with cotrimoxazole and showed rapid clinical improvement. Discussion: The diagnosis of PJP in our patient was based on radiology and an HIV-positive status.  In patients who are not immunocompromised, the diagnosis of PJP is unlikely, and other diagnoses, such as ILD, should be considered. However, in the HIV testing window period of infection, a poor advanced state of HIV could cause a false negative result. Therefore, clinical judgement is essential in suspecting such a result. The empirical treatment course of cotrimoxazole has been shown to provide better clinical outcomes in PJP. Conclusion: The possibility of PJP must be considered in patients with initially HIV-negative results, especially in patients with risk factors and clinical symptoms suggestive of immunocompromise. While some ILD showed similar PJP, the risk factors for ILD and PCP could be distinguishing factors. Retesting for HIV infection can confirm the diagnosis and rule out false-negative results.